Extraction And Chemical Compositions of Ginger (Zingiber Officinale Roscoe) Essential Oils As Cockroaches Repellent - Azhari, H. Nour; Sook, S. Yap; Nour, A. H. (AENSI Publishing, 2017)
Cockroaches are considered to be among natures’ most adaptable creatures, which could pose a serious health issues in many countries. Their inclination for destruction and spreading pathogenic organism and disease has earned mans’ loathing. The study aimed to determine the chemical compositions and potential of the essential oils from genius Zingiber of which Z. officinale (Family: Zingiberaceae) against German cockroaches. The essential oils were obtained by Supercritical Fluid Extraction (SFE) and Soxhlet extraction (SE) methods. Gas Chromatography-Mass Spectrometry (GC-MS) was used to analyse the chemical compositions of the oils. Modified Ebeling Choice-Box test used in the repel test. Four concentrations; 10, 30, 50, and 100%(v/v) of the oils were prepared in water, used tween-80 to dissolve the oils; 1% tween-80 and naphthalene were negative and positive controls, respectively. The oils yields were 4.43 and 0.69 (w/w%) for SFE and SE, respectively. Thirty-five and sixty-six compounds were detected for SE and SFE, respectively. The most major components were: α-zingiberene (16.98 & 13.74%), α-farnesene (12.57 & 10.64%), α-curcumene (8.75 & 8.03%), β-sesquiohellandrene (8.02 & 8.23%), and citral (7.66 & 1.60%), respectively. The repellence depends on oil concentration and the IC50 and IC90 values were 16.0 and 28.0%, respectively, for SFEs’ oil. The study indicates the potential of this essential oil as repellent against the German cockroaches.